2005
DOI: 10.1203/01.pdr.0000169963.94378.b6
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Disorder of Glycosylation Type Id: Clinical Phenotype, Molecular Analysis, Prenatal Diagnosis, and Glycosylation of Fetal Proteins

Abstract: Congenital disorder of glycosylation type Id is an inherited glycosylation disorder based on a defect of the first mannosyltransferase involved in N-glycan biosynthesis inside the endoplasmic reticulum. Only one patient with this disease has been described until now. In this article, a second patient and an affected fetus are described. The patient showed abnormal glycosylation of several plasma proteins as demonstrated by isoelectric focusing and Western blot. Lipid-linked oligosaccharides in the endoplasmic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 29 publications
3
43
0
Order By: Relevance
“…Denecke et al (2005) confirmed that IEF of transferrin in the 19th gestational week was normal in a fetus affected with ALG3-CDG. Other proteins like a1-antitrypsin were also shown to be normally glycosylated in an affected individual in utero.…”
Section: Discussionsupporting
confidence: 61%
“…Denecke et al (2005) confirmed that IEF of transferrin in the 19th gestational week was normal in a fetus affected with ALG3-CDG. Other proteins like a1-antitrypsin were also shown to be normally glycosylated in an affected individual in utero.…”
Section: Discussionsupporting
confidence: 61%
“…More recent patient reports (43)(44)(45) confirm that CDG-1d, apparent from the early weeks of life, is a severe encephalopathy, reminiscent of CDG-Ia and associated with dysmorphic facial and limb features that point at the prenatal expression of this inborn error of metabolism. In one patient the OFC at birth was small (43) and in another it was large (44).…”
Section: Leroymentioning
confidence: 93%
“…Denecke et al (44) offer a useful discussion on fetal versus postnatal hypoglycosylation, as the former was shown to be less pronounced in the affected sibling fetus than in their index patient (44). They prove that prenatal diagnosis also of CDG-Id must depend solely on molecular screening of the ALG3 mutations.…”
Section: Leroymentioning
confidence: 99%
See 1 more Smart Citation
“…They were sizefractionated and analyzed by HPLC. Oligosaccharides linked to dolichol were released, extracted, and analyzed by HPLC essentially as described by Denecke et al (2005).…”
Section: Lipid-linked Oligosaccharide Analysismentioning
confidence: 99%